Manajemen Operasional Digital terhadap faktor-faktor yang berhubungan dengan kejadian Pneumonia di Poliklinik Paru di RSUD Pariaman - Aulia Asman (ADI Bisnis Digital Interdisiplin Jurnal, 2021)
Pneumonia is an acute infection that attacks the lung tissue (alveoli) caused by bacteria, viruses or fungi. Pneumonia is still a potential life threatening hazard and is the 6th cause of death from all causes of death and the first rank as a cause of infectious disease death. The case of pneumonia at the Pulmonary Polyclinic at Pariaman Hospital increased. The initial survey conducted by researchers at the Pulmonary Polyclinic of Pariaman Hospital by interviewing 8 people who visited the Pulmonary Polyclinic where 62.9% of people said they did not know about the definition of pneumonia, the causes of signs and prevention of pneumonia 3 of them suffered from pneumonia they did not finish junior high school and some even went to elementary school, they also said an active smoker. Meanwhile, 37.1% of people said they knew about pneumonia and even its prevention. This study aims to determine the factors associated with the incidence of pneumonia in the Pulmonary Polyclinic of Pariaman Hospital. This type of research is descriptive analytic with a cross sectional study approach. The population in this study were all patients who visited the Pulmonary Clinic at Pariaman Hospital during the study. The sampling technique was accidental sampling. The results showed that there was a relationship. There was a significant relationship between knowledge and attitude of efforts to prevent pneumonia in Pariaman Hospital. The quality of hospital services can be further improved by providing pneumonia counseling and as a reference material for further research related to pneumonia. And. It is hoped that the Health Office will cooperate with the Pariaman Hospital in coordination with the hospital's public health counseling unit (PKM-RS) to provide health education and promotion regarding pneumonia.